Physical activity and quality of life in post-menopausal women with osteoporosis: An integrative review (Research, Society and Development, 2024)
Introduction: In the postmenopausal period, the period after the cessation of menstrual cycles, resulting from ovarian function, the prevalence of osteoporosis and fractures increases according to the period of hormonal disturbance and age. Activities that result in impact are those that most stimulate osteogenesis and thus reduce the loss of bone mass. Objective: To conduct a literature review on physical activity and its impact on the quality of life of post-menopausal women with osteoporosis. Methods: This is an integrative review whose research question was: What are the effects of physical activity on osteoporosis in post-menopausal women with osteoporosis? Results: Studies show positive results related to the practice of physical activity, such as barefoot exercises on a vibrating platform, resistance exercises, strengthening and stretching exercises for the lower limbs, lateral trunk flexors and extensors, and upper limbs, balance exercises, aerobic exercise, among others, as a strategy to improve the quality of life in post-menopausal women with osteoporosis. Conclusion: Studies indicate that regular physical activity, especially resistance and load exercises, plays a fundamental role in minimizing the adverse effects of this phase. Therapeutic modalities such as Pilates and whole-body vibration (WBV) stand out for improving postural balance, strengthening muscles, and increasing bone mineral density, contributing to the prevention of falls and fractures.